2011
DOI: 10.1007/s12185-011-0971-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age, race and decade of treatment on overall survival in a critical population analysis of 40,000 multiple myeloma patients

Abstract: With the availability of novel agents, the overall survival (OS) in patients diagnosed with multiple myeloma (MM) has improved over the last decade. Data on 40,294 MM patients in the years from 1973 to 2003 were obtained from the Surveillance, Epidemiology, and End Results Program (SEER) of the US National Cancer Institute. Statistical analyses evaluating gender, race, age, and year of diagnosis were performed using univariate and multivariate Cox regression models for the OS endpoint. The mean patient age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 32 publications
4
33
1
Order By: Relevance
“…In this study thalidomide was administered in combination with dexamethasone (TD), in combination with melphalan, and prednisone (MPT) or in combination with cyclophosphamide and dexamethasone (CTD). The median age for diagnosis of MM is 68 year [36] and as such this patient population is prone to polypharmacy. The range of additional medication includes pain relief, anti-coagulants and laxatives to treat adverse effects as well as cardiovascular medication, anti-diabetic Fig.…”
Section: Selectivitymentioning
confidence: 99%
“…In this study thalidomide was administered in combination with dexamethasone (TD), in combination with melphalan, and prednisone (MPT) or in combination with cyclophosphamide and dexamethasone (CTD). The median age for diagnosis of MM is 68 year [36] and as such this patient population is prone to polypharmacy. The range of additional medication includes pain relief, anti-coagulants and laxatives to treat adverse effects as well as cardiovascular medication, anti-diabetic Fig.…”
Section: Selectivitymentioning
confidence: 99%
“…It might be due to the existence of several factors which are more efficient on prognosis as well. Although age of diagnosis was reported to be determinant on overall survival in a recent analysis where data of more than 40,000 MM patients were evaluated, it should be kept in mind that the age limit in this analysis was determined to be 75 [7]. In a study by Kleber et al [6] with a focus on comorbidities, chronological patient age, which was observed as significant factor in a single variable analysis, was not as significant as other factors in multivariate analysis and the authors stressed that biological age can substantially differ from the chronological patient age, and that evaluation solely with chronological patient age may lead to false outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…CCI, CCI-age, HCT-SCI and FCI scores were calculated for each patient with these data. While risk groupings were determined as four risk groups for CCI, five risk groups for HCT-SCI, and three risk groups for FCI according to comorbidity scores in original sources [3][4][5]7], three main groups, namely low, intermediate and high, were used in order to make comparisons as in previous studies [4,5] (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Patients with MGUS have a risk of progression to MM of 1 % per year [1]. MM is the second most common haematological malignancy, has a significant community disease burden [2, 3] and is predominantly a disease of the elderly with a median age at diagnosis of approximately 70 years [4]. While the overall prognosis for MM remains poor and the disease is considered incurable with pharmacotherapy, the introduction of new therapies including proteasome inhibitors (PI) and immunomodulatory drugs (IMID) has resulted in a significant improvement in MM outcomes, including the duration of survival [5–8].…”
Section: Introductionmentioning
confidence: 99%